Recent advances in reproductional aspects of Dentex dentex - Pavlidis M.; Loir M.; Fostier A.; Mölsa H.; Scott A. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
The common dentex (Dentex dentex) is a highly valued table fish in the Mediterranean region and elsewhere in the tropics, and is of great potential for mariculture. A basic requirement of intensive farming of any fish species is the ability to control fully the reproductive cycle and spawning in order to ensure a constant supply of high quality eggs and fry. However, basic knowledge on the reproductive biology of common dentex is extremely limited and, therefore, control of its reproduction in captivity poses a bottleneck in the establishment of its commercial culture. Between 1996 and 1998, research (funded by EU, FAIR-CT-95-0407) has been undertaken to provide the scientific and technical basis for effective and reliable reproduction of common dentex. Results on the reproductive biology, hormonal and environmental control of spawning, and broodstock management towards the development of a new species for Mediterranean mariculture are presented herewith.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)